THE KEY FACTORS CONTRIBUTING TO UNEMPLOYMENT AMONG GENERATION Z - Prisca Adela Intan Wulandari, Bernadetta; Darmanto, Darmanto; Haikal Izzulhaq, Muhammad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study examines the factors that contributing to Generation Z's difficulties in securing employment. This research uses secondary data obtained through literature review in the form of previous research articles, information on mass media and social media. The data were analyzed to obtain a comprehensive picture in understanding the factors that influence Generation Z's difficulties in getting a job. Based on the findings, unemployment among Generation Z in Indonesia is a significant issue, driven by three main factors: lack of motivation, low employee well-being, and limited opportunities for self-development. Generation Z's work motivation is influenced by alignment with personal interests, clear goals, and a supportive environment. However, challenges such as weak work ethics, poor communication, and high salary demands without corresponding performance contribute to higher turnover intentions. Additionally, the lack of work-life balance and career development opportunities leads to dissatisfaction among generation Z.